LES THOLÉIITES FINI-TRIASIQUES DE MOHAMMEDIA (MESETA CÔTIÈRE, MAROC): TÉMOINS D’UN VOLCANISME DE RIFT INTRACONTINENTAL AVORTÉ - Khadija Farki; Ghalem Zahour; Hassan El Hadi; Saida Alikouss; Youssef Zerhouni (European Scientific Journal, ESJ, 2014)
The late triassic volcanism of Mohammedia belongs to the Berrechid-El Gara-Benslimane basin. It is manifested by basaltic lava flows intercalated in the triassic silty-sandy conglomerates deposits and in the liassic siltite and evaporatic argillites. Rocks texture is vacuolar, microlithic porphyritic, locally doleritic (ophitic, subophitic to intergranular). Late to post magmatic processes of hydrothermal alteration are responsible of silicification, calcification, chloritisation and epidotization. The studied rocks have geochemical characteristics of continental intraplaque tholeiites similar to their counterparts described in the CAMP province of atlantic circumference. This volcanism could represent a witness of an aborted intracontinental rift, clearly linked to the late-triassic rifting of the Atlantic Ocean.